News Notes. (The Accounting Review, 1973)
The article presents updates on accounting educators in the United States as of October 1, 1973. Joe R. Fritzemeyer, currently Director, Auditing Standards with the American Institute of Certified Public Accountants', has accepted the position of Chairman of the Accounting Department in Arizona State University effective with the Fall Semester 1973. Professors Robert Williamson and John Beverly of the Accounting Department have been promoted to the rank of Associate Professor in the University of Notre Dame. Assistant Professor T. L. Coe has accepted a position at New York University Graduate School of Business for 1973-74. Ruyji Takeda, Professor of Accounting, School of Business Administration, Kobe University, was a visiting research scholar in Duke University during the spring and summer of 1973. America. The Graduate faculties of Catholic University and the Graduate School of Business of Columbia University jointly conducted a conference on "Businesses' Role and Responsibility in Modern Society" August 5-17,1973.